Kedudukan Hukum Perjanjian Pengadaan Barang/Jasa Yang Belum Ditanda Tangani Salah Satu Pihak - Wulandari, Rahajeng; Sudarmanto, Kukuh; Junaidi, Muhammad; Arifin, Zaenal (Universitas Semarang, 2023)
The purpose of this research is to analyze the legal position of the contract of procurement of goods and services that has not been signed by one of the parties by raising a case study based on the cooperation agreement between PT TJB Power Services PLTU Unit 1-2 and PT PLN (Persero) Unit of Manufacture of Tanjung Jati B. This research uses a method of normative jurisprudence approach. The result of this study is an agreement on the procurement of goods and services that has not been signed by one of the parties in PT TJB Power Services has not yet been able to provide legal certainty and justice for the parties. The agreement between PT TjB Power Service and PT PLN (Persero) Unit of Mother Manufacturing Tanjung Jati B must be signed as a form of agreement of the sides. The urgency of this research is that in any agreement must be agreed by the parties, it becomes one of the legal conditions of the agreement as regulated in Article 1320 of the Covenant. The contract of procurement of goods and services between PT TJB Power Services and PT PLN (Persero) Master Unit of Manufacture of Tanjung Jati B must be signed as a form of agreement between the parties. The agreement of proceeding of Goods and Services which has not been signed by one of the parties must be made on the basis of the agreement with the parties with the existence of the legal basis and agreed by the parties in writing as an executable form of the contract for the provision of good and services and legally binding to the party. Tujuan penelitian ini untuk menganalisis kedudukan hukum perjanjian pengadaan barang/jasa yang belum ditandatangani salah satu pihak dengan mengangkat studi kasus berdasarkan perjanjian kerjasama antara PT TJB Power Services PLTU Unit 1-2 dengan PT PLN (Persero) Unit Induk Pembangkitan Tanjung Jati B. Penelitian ini menggunakan metode pendekatan yuridis normatif. Urgensi penelitian ini adalah dalam setiap perjanjian harus disepakati oleh para pihak, hal tersebut menjadi salah satu syarat sahnya perjanjian sebagaimana diatur dalam Pasal 1320 KUHP. Hasil dari penelitian ini adalah perjanjian pengadaan barang/jasa yang belum ditandatangani salah satu pihak di PT TJB Power Services belum dapat memberikan kepastian hukum dan keadilan hukum bagi para pihak. Perjanjian pengadaan barang/jasa antara PT TJB Power Services dengan PT PLN (Persero) Unit Induk Pembangkitan Tanjung Jati B harus ditandatangani sebagai bentuk kesepakatan para pihak. Perjanjian pengadaan barang/jasa yang belum ditandatangani salah satu pihak harus dibuat berdasarkan kesepakatan para pihak dengan adanya dasar hukum dan disepakati para pihak secara tertulis sebagai bentuk dapat dilaksanakannya perjanjian pengadaan barang/jasa dan mengikat secara sah kepada para pihak.